Androgenic signaling systems and their role in behavioral evolution. Issue 184 (November 2018) - Fuxjager, Matthew J.; Schuppe, Eric R.
Highlights: Androgenic signaling systems can evolve to support processes of behavioral adaptation. This evolution can occur with regard to many molecular elements of androgenic signaling pathways. Golden-collared manakinsare birds in which the androgenic system is evolutionarily modified to support courtship behavior. Abstract: Sex steroids mediate the organization and activation of masculine reproductive phenotypes in diverse vertebrate taxa. However, the effects of sex steroid action in this context vary tremendously, in that steroid action influences reproductive physiology and behavior in markedly different ways (even among closely related species). This leads to the idea that the mechanisms underlying sex steroid action similarly differ across vertebrates in a manner that supports diversification of important sexual traits. Here, we highlight the Evolutionary Potential Hypothesis as a framework for understanding how androgen-dependent reproductive behavior evolves. This idea posits that the cellular mechanisms underlying androgenic action can independently evolve within a given target tissue to adjust the hormone's functional effects. The result is a seemingly endless number of permutations in androgenic signaling pathways that can be mapped onto the incredible diversity of reproductive phenotypes. One reason this hypothesis is important is because it shifts current thinking about the evolution of steroid-dependent traits away from an emphasis on circulating steroid levels and toward a focus on molecular mechanisms of hormone action. To this end, we also provide new empirical data suggesting that certain cellular modulators of androgen action—namely, the co-factors that dynamically adjust transcritpional effects of steroid action either up or down—are also substrates on which evolution can act. We then close the review with a detailed look at a case study in the golden-collared manakin ( Manacus vitellinus ). Work in this tropical bird shows how androgenic signaling systems are modified in specific parts of the skeletal muscle system to enhance motor performance necessary to produce acrobatic courtship displays. Altogether, this paper seeks to develop a platform to better understand how steroid action influences the evolution of complex animal behavior.